“The Hidden Door That Leads to Several Moments More”: Finding Context for the Literacy Narrative in First Year Writing - Denise Goldman (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
The literacy narrative has emerged as a useful genre in composition pedagogy because of the perceived bridge it provides between personal narrative and academic literacy. Although there remains disagreement among practitioners with regard to its purpose and efficacy, it continues to be a staple in the writing classroom because it has the potential to help students learn analytical skills while fostering investment through the features of a personal narrative. Recent efforts in the field, especially with regard to questions of transfer of writing, have focused on the benefits of genre and community discourse analysis as a means to help students engage in critical academic analysis that will help them better understand the kind of thinking and writing required for success in the college classroom. In my work with online communities, I find that combining the literacy narrative assignment with community discourse analysis enhances the benefits of both these trajectories as students perform academic investigation of communities with which they feel a personal connection and interest.
Keywords: Literacy; Context; Narrative; Writing